Reaction time in the Agility Test under simulated competitive and noncompetitive conditions - Zemková, E.; Vilman, T.; Kováciková, Z.; Hamar, D. (The Journal of Strength and Conditioning Research, 2013)
The study evaluates a reaction time in the Agility Test under simulated competitive and noncompetitive conditions. A group of 16 fit men performed, in random order, 2 versions of the Agility Test: non-competitive Agility Single and Agility Dual in form of simulated competition. In both cases, subjects had to touch, as fast as possible, with either the left or the right foot 1 of 4 mats located in 4 corners outside of an 80 cm square. Mats had to be touched in accordance with the location of the stimulus in one of the corners of the screen. The test consisted of 20 visual stimuli with random generation of their location on the screen and time generation from 500 to 2,500 milliseconds. The result was total reaction time (RT) for all 20 reactions measured by a PC-based system FiTRO Agility Check. Results showed significantly (p < 0.01) better RT in the Agility Dual than in the Agility Single Test (690.6 ± 83.8 milliseconds and 805.8 ± 101.1 milliseconds, respectively). Further comparisons of RT under noncompetitive and simulated competitive conditions for the best 8 subjects proceeded in the second match showed a decrease from 781.3 ± 111.2 milliseconds to 693.6 ± 97.8 milliseconds in the first match and to 637.0 ± 53.0 milliseconds in the second match. It may be concluded that RT is better when the Agility Test is performed in simulated competitive than noncompetitive conditions. The Agility Test in form of competition may be used for children and young athletes to enhance their attention level and motivation.